Efeitos derrame da mineração, violências cotidianas e resistências em Conceição do Mato Dentro-MG - Clarissa Godinho Prates (2017)
Minas-Rio is a mining project owned by Anglo American which comprises a mine and adjacent structures in Conceição do Mato Dentro, Alvorada de Minas and Dom Joaquim; a pipeline that runs through 33 municipalities between the states of Minas Gerais and Rio de Janeiro; and a port, in São João da Barra-RJ. Since the beginning of the licensing process, the project has been the target of protests and opposition by farmers and social movements over human rights violations environmental degradation. In 2014, these claims were met with violence and overall disregard during a hearing that granted Anglo American the License to Operate despite its non-compliance with 368 legal requirements. Given this broader context, this dissertation analyzes the day to day violence produced by mining, considering the affected communities around the Minas-Rio project. From the narratives of three local subjects, themselves entangled with processes of violence and resistance, I approach the themes of social suffering, the effects of transformations of place on the body and the explicit violence against those who oppose the project.